Contributions of street foods to dietary intakes of traders in selected open markets in Uyo, Akwa Ibom State, Nigeria - Ekerette, Nkereuwem Ndaeyo; Alozie, Yetunde Ezinwanyi; Etim, Toro Efiok (World Nutrition, 2025)
Street food (SF) consumption is gaining popularity across urban settings, making significant contributions to dietary intake, even in low-income settings. The objective of this study was to assess the contributions of SFs to the dietary and nutritional intakes of market traders within the Uyo metropolis. This was a cross-sectional study. Participants (421, with an average age of 41.2±11.5) were selected using probability sampling to be representative of traders who were active over the past two years in Uyo. The multi-pass 24-hour dietary recall methodology was used to assess usual dietary intakes. Total Dietary Assessment Software was used to derive energy and nutrient intake values from food intake information. Energy intake was compared with the Estimated Energy Requirement, and nutrient intakes were assessed against their respective Recommended Dietary Allowances to determine percentage adequacy. In their overall diets, traders met the recommended intake level for carbohydrate, but generally had suboptimal intakes of energy, dietary fibre, vitamin A, and calcium in both men and women, as well as iron among women aged 19-50 years. A majority (74.6%) consumed SFs. Among SF consumers, percentage contributions of SFs to energy and nutrient intakes among men and women, respectively, were as follows: energy (34.9% and 28.5%), carbohydrate (108% and 68.8%), protein (51.2% and 32.8%), dietary fibre (0.0%-23.7% and 26.0%-31.0%) and calcium (16.1% and 6.5%-7.8%). Overweight, general, and abdominal obesity were 30.2%, 4.8%, and 44.5%, respectively. Increased BMI was significantly related to reasons for SF consumption (p < 0.001). Abdominal obesity had significant associations with the forms of SFs commonly consumed and with the amounts spent on SF consumption (p < 0.001), respectively. Traders had suboptimal intake levels for most nutrients and met substantial proportions of their daily energy and nutrient requirements through SF consumption. Increased BMI and abdominal obesity were prevalent and associated with SF consumption practices. Policy regulations that selectively promote the preparation and sales of healthier meals by vendors in the marketplace are warranted.